Vpliv nanotehnologije na razvoj zdravil - Kristl, Julijana (Farmacevtski vestnik, 2012)
Nanotechnology has a significant impact on the development of nanomedicines, which represent formulation bionanosystems, targeting drug delivery and tissuee ngineering including nanoelectronic biosenzors. Preparation, characterization and evaluation need new sophisticated methods, procedures and equipments, different from known before. A brief review of novel trends in the scope of nanotechnology and nanomedicine is presented, their implementation and some promising techniques, which could thoroughly change our previous understanding of healing. Countries around the world have seized on the opportunities offered by nanotechnology for significant breakthroughs in development, innovation and marketing of nanomedicine. Their strategies are adapted on dynamic, fast moving changes in view to collaboration and competition. Special attention is focused on toxicological and regulatory aspect of nanomedicine.
Keywords: dostavni sistemi; nanodelci; nanotehnologija; nanozdravila